Cytochrome P450 2D6 genotype–phenotype characterization through population pharmacokinetic modeling of tedatioxetine - Frederiksen, Trine; Areberg, Johan; Schmidt, Ellen; Stage, Tore Bjerregaard; Brøsen, Kim (CPT: pharmacometrics and systems pharmacology, 2021)
The cytochrome P450 (CYP) 2D6 enzyme exhibits large interindividual differences in metabolic activity. Patients are commonly assigned a CYP2D6 phenotype based on their CYP2D6 genotype, but there is a lack of consensus on how to translate genotypes into phenotypes, causing inconsistency in genotype‐based dose recommendations. The aim of this study was to quantify and compare the impact of different CYP2D6 genotypes and alleles on CYP2D6 metabolism using a large clinical data set. A population pharmacokinetic (popPK) model of tedatioxetine and its CYP2D6‐dependent metabolite was developed based on pharmacokinetic data from 578 subjects. The CYP2D6‐mediated metabolism was quantified for each subject based on estimates from the final popPK model, and CYP2D6 activity scores were calculated for each allele using multiple linear regression. The activity scores estimated for the decreased function alleles were 0.46 (CYP2D6*9), 0.34 (CYP2D6*10), 0.01 (CYP2D6*17), 0.65 (CYP2D6*29), and 0.21 (CYP2D6*41). The CYP2D6*17 and CYP2D6*41 alleles were thus associated with the lowest CYP2D6 activity, although only the difference to the CYP2D6*9 allele was shown to be statistically significant (p = 0.02 and p = 0.05, respectively). The study provides new in vivo evidence of the enzyme function of different CYP2D6 genotypes and alleles. Our findings suggest that the activity score assigned to CYP2D6*41 should be revisited, whereas CYP2D6*17 appears to exhibit substrate‐specific behavior. Further studies are needed to confirm the findings and to improve the understanding of CYP2D6 genotype–phenotype relationships across substrates.